Rhinoviruses in pandemic. Santa Fe city, Argentina. Biennium 2020-2021 (Actualizaciones en Sida e Infectología, 2023)
In the context of the COVID-19 pandemic, in 2020, the influenza-like illness Sentinel Unit (ILI-SU) (Santa Fe, Argentina), integrated clinical and laboratory surveillance of SARS-CoV-2 and Rhinovirus (HRV) to the usual surveillance of Influenza and other respiratory viruses (ORV). The objective of this cross-sectional and retrospective study was to describe the clinical- epidemiological characteristics of ILI cases of Santa Fe city, who had a confirmed HRV diagnosis during 2020- 2021, by the ILI-SU. Of a total of 600 ILI cases whose samples were analyzed, more than 50.0% were women; and the highest proportion was concentrated in the group between 15 and 39 years of age (40.2%). 33.7% of the cases registered at least one comorbidity or risk factor, among which arterial hypertension, asthma, diabetes, obesity and COPD were the most frequent. In addition to fever and cough, the predominant signs/symptoms were sore throat, myalgia and headache. The percentage of positivity was 41.3% in 2020, 27.8% in 2021, and 35.5% in 2020-2021. Of the biennium positive samples (213), 59.0% were SARS-CoV-2, 40.0% HRV, and 1.0% ORV. The highest proportion of SARS-CoV-2 positive diagnoses were concentrated in patients 15 years of age and older, while the highest proportion of HRV positive diagnoses were concentrated in patients under 15 years of age. The periods in which the circulation of HRV predominated did not predominated SARS-CoV-2, and vice versa. The contribution to the real burden of respiratory viral infections and its impact on public health, highlight the importance of sustaining HRV surveillance.
Keywords: Surveillance, SARS-CoV-2, Rhinovirus